Behavioral trace data in an online learning environment as indicators of learning engagement in university students - Winter, Marc; Mordel, Julia; Mendzheritskaya, Julia; Biedermann, Daniel; Ciordas-Hertel, George-Petru; Hahnel, Carolin; Bengs, Daniel; Wolter, Ilka; Goldhammer, Frank; Drachsler, Hendrik; Artelt, Cordula; Horz, Holger (Frontiers in Psychology, 2024)
Learning in asynchronous online settings (AOSs) is challenging for university students. However, the construct of learning engagement (LE) represents a possible lever to identify and reduce challenges while learning online, especially, in AOSs. Learning analytics provides a fruitful framework to analyze students' learning processes and LE via trace data. The study, therefore, addresses the questions of whether LE can be modeled with the sub-dimensions of effort, attention, and content interest and by which trace data, derived from behavior within an AOS, these facets of LE are represented in self-reports. Participants were 764 university students attending an AOS. The results of best-subset regression analysis show that a model combining multiple indicators can account for a proportion of the variance in students' LE (highly significant R2 between 0.04 and 0.13). The identified set of indicators is stable over time supporting the transferability to similar learning contexts. The results of this study can contribute to both research on learning processes in AOSs in higher education and the application of learning analytics in university teaching (e.g., modeling automated feedback).